Mammography Screening by Race/Ethnicity Among U.S. Servicewomen, 2009–2010 - Enewold, Lindsey (2012)
BACKGROUND: Mammography screening has been shown to vary by race/ethnicity and is often thought to result from variations in access to healthcare. The objective of this study was to compare the prevalence of recent mammography screening among U.S. active duty servicewomen by race/ethnicity using administrative claim data from the Military Health System, which provides beneficiaries with equal access to medical care. METHODS: Mammography screening use during fiscal years 2009-2010 among non-Hispanic white, non-Hispanic black, Asian/Pacific Islander (API) and Hispanic servicewomen was analyzed using logistic regression. RESULTS: Overall the prevalence of mammography screening during the study period was 61%. In comparison to non-Hispanic white servicewomen, API (OR=1.08; 95% CI=0.94-1.23) and Hispanic servicewomen (OR=0.97; 95% CI=0.85-1.11) were as likely and non-Hispanic black servicewomen were more likely to have a screening mammogram (OR=1.09; 95% CI=1.01-1.18). Screening mammography also increased with age, was highest in the Navy, was higher among officers than enlisted personnel, and did not differ by marital status. CONCLUSION: Although screening was slightly higher for non-Hispanic blacks than non-Hispanic whites, in general, racial/ethnic differences in mammography screening were not substantial in an equal access system.